A model for fluid stiction of quickly separating circular plates. (June 2014) - Resch, M; Scheidl, R
Fluid stiction is a force which is created by the average pressure difference between a fluid-filled, narrow, quickly opening gap and the surrounding pressure. It plays a negative role in compressor valve technology and in fast switching valves, since it hinders an immediate response of the valves to a changing driving force situation. In this paper, the axisymmetric fluid stiction problem is studied by analytical mathematical models and experiments performed on a specific test rig. The study shows that the stiction force in narrow gaps is dominated by the viscous flow as described by the Reynolds equation for lubricating gaps and by cavitation which occurs in a centre region if the gap opening speed exceeds a critical value. The cavitation zone first extends and then shrinks and, finally, gives rise to complex oscillation phenomena due to the impact of the fluid when the cavitation zone collapses. It was found experimentally that fluids can create negative pressure for very short time. Measures to limit the stiction force are a large initial gap height or additional fluid supply channels from the surrounding to the gap.